Low dose of isotretinoin: A comprehensive review. Issue 2 (20th February 2020) - Abdelmaksoud, Ayman; Lotti, Torello; Anadolu, Rana; Goldust, Mohamed; Ayhan, Erhan; Dave, Dharmendra D.; Vestita, Michelangelo; Ebik, Berat; Gupta, Mrinal
Abstract: Isotretinoin is a first‐generation retinoid initially approved for the treatment of severe cases of acne vulgaris (nodulocystic acne). Because of its broad anti‐inflammatory and immunomodulatory properties, it has been used beyond its initial approval in a myriad of other indications. Adverse effects of isotretinoin vary from xerosis to teratogenicity. Herein, we reviewed the literature, through date‐unlimited PubMed search, from inception till December 2019, using the following search terms: "low‐dose isotretinoin" and "dermatology, " "isotretinoin and safety, " "isotretinoin, off‐label uses, " "isotretinoin and male fertility, " "isotretinoin, iPLEDGE system, " aiming to deliver a therapeutic update relevant to clinical practice. All English‐language articles were considered with no limitation based on the articles' type. Low‐dose isotretinoin is not limited to old and novel dermatological conditions, but also showed promising results in the field of infertility and safety in the field of gastroenterology. We also highlight on the safety profile of the drug and experts' recommendations to enhance safety measures to decrease fetal risk while on isotretinoin.